Peningkatan Hasil Belajar Tematik melalui Penerapan Model Pembelajaran Kooperatif Tipe Word Square pada Murid Kelas V MIS Muhamadiyah Sibatua Kecamatan Pangkaje’ne Kabupaten Pangkep - Dita Amelia Azmi; Risky Nuramelyah; Idawati Fadollah; Tarman A. Arif (Departement of Mathematics Education, 2023)
The research objective was to improve thematic learning outcomes through the application of the word square cooperative learning model in class V MIS Muhammadiyah Sibatua, Pangkaje'ne District, Pangkep Regency. The formulation of the problem of this research is how to increase thematic learning outcomes through the application of the Word Square type cooperative learning model for fifth grade students, Mis Muhamadiyah Sibatua, Pangkaje'ne District, Pangkep Regency. The classroom action research procedure used refers to the action research methodology, namely (1) planning, (2) action implementation, (3) observation and evaluation, (4) reflection, which is carried out in 2 cycles. The evaluation results of cycle 1 showed that 6 students or 37.5% got the highest scores, 5 students or 31.25% got high scores, 2 students or 12.5% ​​got medium and low scores and 1 student or 6.25 % who scored very low. The average value of all students was 54% so that it was categorized as High and the results of cycle 2 showed that the questions increased to 89.39%, students who worked on practice questions to 89.39%, and students who needed guidance 16.66%, while students who did other activities that are not relevant to learning decreased to 10.60%. This shows an increase in student learning outcomes. From this classroom action research it can be concluded that independent practice can improve mastery of the material The Importance of Healthy Food for the Body Sub Theme 2 for class V MIS Muhammadiyah Sibatua Odd Semester 2022/2023 Academic Year. The suggestions in this study are as follows: Elementary school teachers need to apply the Word Square cooperative learning model as one of the learning methods in the classroom because this model is proven to improve students' ability to understand the material.